Wittgenstein and Psychoanalysis: Image and Imagination in Wittgenstein and Freud - Carlo Sini (The European Journal of Psychoanalysis, 2014)
In this text I shall develop a parallel reading of Wittgenstein’s picture theory (Tractatus logico-philosophicus) and Freud’s theory of the vesicle (Beyond the pleasure principle), trying to show the substantial analogies and the identical target of their trajectories, namely the idea that images are things and that signs are the matter out of which our “mind” (Wittgenstein) or “psychic life” (Freud) emerges.
Keywords: Diagnosis; language; Self-understanding; therapy; transformation